2002
DOI: 10.1038/sj.leu.2402458
|View full text |Cite
|
Sign up to set email alerts
|

Role of tumor suppressor genes in the development of adult T cell leukemia/lymphoma (ATLL)

Abstract: Adult T cell leukemia/lymphoma (ATLL) is one of the peripheral T cell malignant neoplasms strongly associated with human T cell leukemia virus type-I (HTLV-I). Although the viral transactivating protein Tax

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 249 publications
0
52
1
Order By: Relevance
“…Alteration of the p53 gene has been observed in 40% of ATL cases (Kinoshita et al, 1992;Sakashita et al, 1992;Yamato et al, 1993), while alterations in p15 INK4B , p16 INK4A , and retinoblastoma (Rb) genes occur in about 30, 35, and 5% of ATL cases, respectively (Hatta et al, 1997a;Suzuki et al, 1999a;Hatta and Koeffler, 2002). Although rare, mutation of p18 INK4C has also been identified in some ATL cells (Hatta et al, 1997b).…”
Section: Genome Instability and Htlv-i Infectionmentioning
confidence: 99%
“…Alteration of the p53 gene has been observed in 40% of ATL cases (Kinoshita et al, 1992;Sakashita et al, 1992;Yamato et al, 1993), while alterations in p15 INK4B , p16 INK4A , and retinoblastoma (Rb) genes occur in about 30, 35, and 5% of ATL cases, respectively (Hatta et al, 1997a;Suzuki et al, 1999a;Hatta and Koeffler, 2002). Although rare, mutation of p18 INK4C has also been identified in some ATL cells (Hatta et al, 1997b).…”
Section: Genome Instability and Htlv-i Infectionmentioning
confidence: 99%
“…Rb is epigenetically and genetically inactivated in many cancers (Scrable et al, 1990). In cell cycle studies, many have found that Tax accelerate G1 to S transition (Neuveut et al, 1998;Schmitt et al, 1998;Kehn et al, 2004), providing initial clues that HTLV-1 may inactivate Rb function (Hangaishi et al, 1996;Hatta and Koeffler, 2002). There may be two explanations for how HTLV-1 inactivates Rb.…”
Section: Tax and Rbmentioning
confidence: 99%
“…An additional disruptive effect of Tax emanates from its impact on the ability of the cell-cycle machinery to regulate DNA replication and cell division (reviewed in Mesnard and Devaux, 1999;Jeang, 2000, 2002;Yoshida, 2001;Hatta and Koeffler, 2002). Progression through various stages of the cell cycle is controlled by different cyclin/cdk (cyclin-dependent kinase) complexes.…”
Section: Cell-cycle Dysregulationmentioning
confidence: 99%